Assessment of COX-2 expression presence and severity by immunohistochemical method in patients with chronic active gastritis and intestinal metaplasia - Gülbanu ERKAN,; İpek Işık ERKAN,; Uğur KANDİLCİ,; Ayşe DURSUN, (Turkish Journal of Gastroenterology, 2019)
-